Topography of slowed dark adaptation in pseudoxanthoma elasticum: PROPXE study report 1 - Pfau, Kristina; Ansari, Georg; Michels, Stephan; Dysli, Chantal; Liakopoulos, Sandra; Burghaus-Zhang, Jana; Al-Sheikh, Mayss; Garweg, Justus G.; Quinodoz, Mathieu; Kaminska, Karolina; Cancellieri, Francesca; Rivolta, Carlo; et al. (Investigative ophthalmology & visual science, 2025)
To determine the prevalence and spatial pattern of rod and cone dysfunction in patients with pseudoxanthoma elasticum (PXE) and to correlate these with Bruch's membrane (BrM) calcification. PXE is a rare genetic disorder that causes calcification of Bruch's membrane, which eventually leads to loss of central vision. Understanding the functional implications of BrM calcification is crucial for developing effective treatments. In this prospective natural history study (PROPXE, ClinicalTrials.gov ID: NCT05662085), performed at a tertiary referral center, 26 patients with PXE (14 women, 12 men; median age, 55 years; interquartile range, 43-59 years), diagnosed according to the Plomp criteria, underwent comprehensive ophthalmic evaluations, including best-corrected visual acuity (BCVA), contrast sensitivity testing, and multimodal imaging. Dark adaptometry was tested following a 59% rhodopsin bleach at 8°, 15°, 30°, and 46° eccentricity from the fovea along the temporal retina. The eye without a history of exudative macular neovascularization (MNV) or the better-seeing eye was selected as the study eye. Of 26 participants, 12 had no history of exudative MNV in the study eye, while 14 had previous or current treatment for MNV with a median BCVA of −0.07 logMAR and 0.11 logMAR, respectively. In the macula at 8° eccentricity, rod intercept time (RIT) was prolonged in 83.3% of nonexudative and 92.9% of exudative eyes, while BCVA and cone thresholds at 8° eccentricity were affected in only 42.3% and 65.4% of eyes. The delay in RIT was most pronounced in regions at risk of calcification and increased markedly with age. In addition, prolonged cone recovery time constants were evident that correlated with RIT. Patients with PXE exhibit significant slowing of both cone- and rod-mediated dark adaptation, particularly in regions prone to BrM calcification. These findings suggest that dark adaptometry and assessment of BrM calcification can serve as clinical tools for evaluating disease severity and monitoring progression in PXE, enabling earlier interventions before the onset of exudative MNV or atrophy.